Maximal aerobic power characteristics of male professional soccer players, 1989-2012 - Tonnessen, E.; Hem, E.; Leirstein, S.; Haugen, T.; Seiler, S. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The purpose of this investigation was to quantify maximal aerobic power (VO2max) in soccer as a function of performance level, position, age, and time of season. In addition, the authors examined the evolution of VO2max among professional players over a 23-y period. Methods: 1545 male soccer players (22 ± 4 y, 76 ± 8 kg, 181 ± 6 cm) were tested for VO2max at the Norwegian Olympic Training Center between 1989 and 2012. Results: No differences in VO2max were observed among national-team players, 1st- and 2nd-division players, and juniors. Midfielders had higher VO2max than defenders, forwards, and goalkeepers (P < .05). Players 2max than 23- to 26-y-old players (P = .016). The players had 1.6% and 2.1% lower VO2max during off-season than preseason (P = .046) and in season (P = .021), respectively. Relative to body mass, VO2max among the professional players in this study has not improved over time. Professional players tested during 2006-2012 actually had 3.2% lower VO2max than those tested from 2000 to 2006 (P = .001). Conclusions: This study provides effect-magnitude estimates for the influence of performance level, player position, age, and season time on VO2max in men`s elite soccer. The findings from a robust data set indicate that VO2max values ~62-64 mL/kg·min fulfill the demands for aerobic capacity in men`s professional soccer and that VO2max is not a clearly distinguishing variable separating players of different standards.